Lateral Hypothalamic GABAergic Neurons Encode and Potentiate Sucrose's Palatability - Aketzali Garcia; Alam Coss; Jorge Luis-Islas; Liliana Puron-Sierra; Monica Luna; Miguel Villavicencio; Ranier Gutierrez (Frontiers in Neuroscience, 2021)
Sucrose is attractive to most species in the animal kingdom, not only because it induces a sweet taste sensation but also for its positive palatability (i.e., oromotor responses elicited by increasing sucrose concentrations). Although palatability is such an important sensory attribute, it is currently unknown which cell types encode and modulate sucrose's palatability. Studies in mice have shown that activation of GABAergic LHAVgat+ neurons evokes voracious eating; however, it is not known whether these neurons would be driving consumption by increasing palatability. Using optrode recordings, we measured sucrose's palatability while VGAT-ChR2 transgenic mice performed a brief access sucrose test. We found that a subpopulation of LHAVgat+ neurons encodes palatability by increasing (or decreasing) their activity as a function of the increment in licking responses evoked by sucrose concentrations. Optogenetic gain of function experiments, where mice were able to choose among available water, 3% and 18% sucrose solutions, uncovered that opto-stimulation of LHAVgat+ neurons consistently promoted higher intake of the most palatable stimulus (18% sucrose). In contrast, if they self-stimulated near the less palatable stimulus, some VGAT-ChR2 mice preferred water over 18% sucrose. Unexpectedly, activation of LHAVgat+ neurons increased quinine intake but only during water deprivation, since in sated animals, they failed to promote quinine intake or tolerate an aversive stimulus. Conversely, these neurons promoted overconsumption of sucrose when it was the nearest stimulus. Also, experiments with solid foods further confirmed that these neurons increased food interaction time with the most palatable food available. We conclude that LHAVgat+ neurons increase the drive to consume, but it is potentiated by the palatability and proximity of the tastant.